ANTI-ARTHRITIC EFFECT OF THYMOQUINONE IN COMPARISON WITH METHOTREXATE ON PRISTANE INDUCED ARTHRITIS IN FEMALE SPRAGUE DAWLEY RATS - Faisal, Rizwan; Ahmad, Nisar; Fahed, Yahya Saleem; Chiragh, Sadia (Journal of Ayub Medical College Abbottabad, 2018)
Background: Rheumatoid arthritis inflammatory joint disease which is chronic in nature. Since long various researches are carried out to find the remedy of this disease but still a lot of work needed to be done. Methods: This comparative study was performed from March to August 2013 at Postgraduate Medical Institute, Lahore. A total of thirty-two female Sprague-Dawley rats were randomly divided into four equal groups (n=8); group A was kept as healthy control, group B was kept as positive control, group C was treated with thymoquinone and group D was treated with methotrexate. Arthritis developed within two weeks in group B, group C and group D after giving a single shot of pristane intradermally. Treatment was started on day 15. At day 30 (time of dissection) paw weight and histopathological sections of ankle joints of all the animals were taken. Results: The results shown significant rise in paw weight and score of histopathological parameters in group B, group C and group D when compared with healthy control rats. Thymoquinone and methotrexate treated groups shown reduction in paw weight and score of histopathological parameters when compared to positive control rats with p-value 0.001each. The difference between groups C and D was insignificant (p-value 0.062). Conclusion: Study results supported the anti-inflammatory and disease modifying activities of thymoquinone as it significantly reduces both paw weight and histological parameters of joint inflammation. Keywords: Thymoquinone; Pristane; Paw weight; Joint histopathology; Rheumatoid arthritis; Methotrexate